Wisdom and creation in Jesus Ben Sira : a study of the role of Dame Wisdom in Sirach 1:1-10 and chapter 24 - Rogers, Jessie(Jessie Florence) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1994.